Development of ocular hypertension and persistent glaucoma after intravitreal injection of triamcinolone - M Selim Kocabora (Dove Medical Press, 2008)
M Selim Kocabora, Cemil Yilmazli, Muhittin Taskapili, Gokhan Gulkilik, Sahan DurmazVakif Gureba Education and Research Hospital, Istanbul, TurkeyPurpose: This study evaluates intraocular pressure (IOP) elevation secondary to intravitreal injection of triamcinolone acetonide (IVTA) and discusses its management.Methods: The records of 175 patients who underwent IVTA treatment and regular eye examinations in the period 2003–2006 were reviewed. One hundred and twenty-two of these patients were included in the study, of which 147 eyes that received IVTA (4 mg/0.1 ml) were followed for at least 9 months. Mean IOPs observed after IVTA injection as well as IOP elevations defined as moderate (≥5 mm Hg), important (≥10 mm Hg) and severe (>25 mm Hg) during the follow-up period were evaluated and compared statistically.Results: Overall, the mean IOPs following IVTA injection were statistically significantly higher than the preinjection IOP (15.8 ± 2.6), after the first hour (17.7 ± 2.9), the first week (18.7 ± 4.1), the first month (19.6 ± 6.2), the second month (19.1 ± 6.1), the third month (18.0 ± 4.1), the sixth month (17.3 ± 4.0), and the ninth month (17.0 ± 2.7), but not after the first day (16.3 ± 7.6). Important IOP elevations were observed mostly in the first (17.7%) and second months (10.2%). In 40 (27.7%) eyes, topical antiglaucomatous therapy was needed and 7 later required surgical intervention to lower the IOP. Of the remaining 33 eyes, topical treatment was continued in 14 (9.5%) because of IOPs ≥20 mm Hg.Conclusion: The persistence of IOP elevation beyond the IVTA clearance period and the development of intractable secondary glaucoma requiring surgical intervention substantiate the need for careful consideration of IVTA indication and follow-up.Keywords: intravitreal triamcinolone, intraocular pressure, steroid-induced glaucoma